The associate - Margolin, Phillip (New York : HarperCollins Publishers, 2001)
Daniel Ames, an associate with Portland's most prestigious law firm, finds himself fighting to save his reputation and his life when he decides to investigate claims that Gellar Pharmaceuticals, one of the firm's biggest clients, is producing a drug that allegedly causes birth defects.
Keywords: Pharmaceutical industry -- Fiction; Detective and mystery fiction